Nota técnica 2: An equal Variance Test - Djolov, George (Estudios de Economía, 2016)
This article introduces (and hopes to encourage thereby) the econometrics practitioner to (use) a homoscedasticity test referred to in the field of statistics as the modified Levene test. Econometrics orthodoxy (from University to practice level) has focused mainly on three heteroscedasticity tests, namely the Goldfeld-Quandt (GQ), Breusch-Pagan-Godfrey (BPG), and the White (W) test. The difference between the aforementioned tests and the test elaborated on in this article is that the former are for regression whereas the latter is for ANOVA –analysis of variance– situations.